Pitaya fruit quality (Hylocereus undatus [Haworth] Britton & Rose) according to physiological maturity. A review - Ortiz, Thiago Alberto; Takahashi, Lúcia Sadayo Assari (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The pitaya fruit has occupied a growing niche in the fruit market because its organoleptic characteristics and rusticity have attracted the attention of consumers and producers, respectively. The organoleptic and nutritional quality of fruits are due to the maturity stage. Therefore, determining the period in which the fruits reach physiological maturity is important since it aids the planning of the harvest and fruit quality control. In this sense, the aim of this review was to establish the ideal period for harvesting pitaya fruits (Hylocereus undatus) by determining the physiological maturity point. For this species, the number of days from anthesis to full development of the fruit has been the most reliable variable to determine harvest timing. With this designation, it is possible to indicate the stage (physiological maturity) in which the fruits present characteristics that are favorable to the species, for example, color, soluble solids content, ratio, and others. The place of production and edaphoclimatic conditions can interfere and cause variation in the period in which fruits reach physiological maturity. Some studies in Mexico have confirmed that the physiological maturation of pitaya fruits occurs between 25 and 31 days after anthesis (DAA). Other research, including in Brazil, has confirmed that this point occurred from 28 to 32 DAA. Thus, based on the scientific studies in the literature, it is recommended to harvest pitaya fruits between 25 and 32 DAA to avoid losing the commercial value of fruits.